Dielectric Relaxation Studies of the System Copper(II) Soap-Non-Polar Solvent at Microwave Frequencies - Mehta, V.P.; Khanna, R.K.; Talesara, P.R.; Sharma, Rashmi (Asian Journal of Chemistry, 2010)
There has been a renaissance of interest to understand micellar characterization of surfactant solutions using dielectric relaxation studies. Measurements of the complex dielectric constant of the system: Copper(II) soap(C6 and C8)–Non-polar solvent (benzene and carbon tetrachloride) have been carried out at 8.82 GHz and 8.86 GHz frequencies at 30ºC. The results have been analysed in terms of dielectric relaxation time (τ) evaluated using the single frequency concentration variation method enunciated by Gopal Krishna.